The Cambridge Handbook of Consumer Psychology (Cambridge handbooks in psychology, 2015)
Why do consumers make the purchases they do, and which ones make them truly happy? Why are consumers willing to spend huge sums of money to appear high status? This handbook addresses these key questions and many more. It provides a comprehensive overview of consumer psychology, examining cutting-edge research at the individual, interpersonal, and societal levels. Leading scholars summarize past and current findings and consider future lines of inquiry to deepen our understanding of the psychology behind consumers' decision making, their interactions with other consumers, and the effects of societal factors on consumption. The Cambridge Handbook of Consumer Psychology will act as a valuable guide for faculty as well as graduate and undergraduate students in psychology, marketing, management, sociology, and anthropology